Post-WWI military disarmament and interwar fascism: Evidence from Sweden - Heléne Berg; Matz Dahlberg; Kåre Vernby (Uppsala University, Department of Economics, 2016)
The emergence of anti-democratic movements is a central puzzle to social science. We study a novel and rich dataset covering Swedish municipalities during the interwar years and find a strong link between the presence of a military garrison and the emergence of fascist parties. We interpret these results as suggesting that fascist mobilization in Sweden was driven by discontent with the process of disarmament brought about by democratization. By contrast, economic hard times, as captured by local poverty and the size of the tax base, seem to have little connection with such parties. We relate these results to influential theories of democratization.
urn:nbn:se:uu:diva-311432
Keywords: N44; 330; Democracy; Interwar fascism; Disarmament